Effects of Un-transposed UHV Transmission Line on Fault Analysis of Power Systems - 王安宁 陈青 周占平 (Transactions of Tianjin University, 2008)
The conventional fault analysis method based on symmetrical components supposes that the three-phase parameters of un-transposed transmission line are symmetrical in case of fault. The errors caused by the method with the symmetrical distributed parameter circuit model as the equivalent circuit of the un-transposed ultra high voltage（UHV） transmission line were studied under both normal operation and fault,and the corresponding problems arising were pointed out. By contrast with electromagnetic transient and power electronics（EMTPE） simulation results with the asymmetrical distributed parameter circuit model of un-transposed line, it is shown that the conventional method cannot show the existence of negative and zero sequences before fault happening and there are many errors on voltage and current after fault happening which are different with fault types. The error ranges of voltage and current are 2.13%— -81.13% and -7.82%— -86.15%, respectively.